185k views
3 votes
What is the solution to this equation?

3(a−4)+1=9−a


a = 3

a = 5

a = 6

a = 10

2 Answers

5 votes

Answer,

a = 5

Explanation,

Step 1: Simplify both sides of the equation

3(a−4) + 1 = 9 − a

(3)(a) + (3)(-4) + 1 = 9 + -a (Distribute)

3a + − 12 + 1 = 9 + − a

(3a) + (−12 + 1) = − a + 9 (Combine Like Terms)

3a + −11 = −a + 9

3a − 11 = − a + 9

Step 2: Add a to both sides

3a − 11 + a = −a + 9 + a

4a − 11 = 9

Step 3: Add 11 to both sides

4a − 11 + 11 = 9 + 11

4a = 20

Step 4: Divide both sides by 4

4a/4 = 20/4

a = 5


Hope this helps :-)

User Xcodian Solangi
by
5.3k points
4 votes

Equation: 3(a-4)+1=9-a

First, distribute.

3a-12+1=9-a

Combine like terms (12+1).

3a-13=9-a

Add a to both sides.

4a-13=9

Add 13 to both sides.

4a=22

Divide both sides by 4.

a=5.5

Your answer would be a=5.

I hope this helps :)

User Eveline
by
5.5k points